2012
DOI: 10.2147/ijn.s35575
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and evaluation of SiO2-deposited stearic acid-g-chitosan nanoparticles for doxorubicin delivery

Abstract: Purpose: Both polymer micelles and mesoporous silica nanoparticles have been widely researched as vectors for small molecular insoluble drugs. To combine the advantages of copolymers and silica, studies on the preparation of copolymer-silica composites and cellular evaluation were carried out. Methods: First, a stearic acid-g-chitosan (CS-SA) copolymer was synthesized through a coupling reaction, and then silicone oxide (SiO 2 )-deposited doxorubicin (DOX)-loaded stearic acid-g-chitosan (CS-SA/SiO 2 /DOX) nano… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 22 publications
0
13
0
Order By: Relevance
“…17 For instance, pore size distribution can be changed to alter release rate of encapsulated drug. 18 Sol-gel technology is also cost effective, biocompatible, and nontoxic. 17 Our platform has been employed to encapsulate agents ranging from nitric oxide for infection and wound healing 15,19 to amphotericin B for fungal burn wound infections 20 to sildenafil for erectile dysfunction.…”
Section: Introductionmentioning
confidence: 99%
“…17 For instance, pore size distribution can be changed to alter release rate of encapsulated drug. 18 Sol-gel technology is also cost effective, biocompatible, and nontoxic. 17 Our platform has been employed to encapsulate agents ranging from nitric oxide for infection and wound healing 15,19 to amphotericin B for fungal burn wound infections 20 to sildenafil for erectile dysfunction.…”
Section: Introductionmentioning
confidence: 99%
“…The change in size, shape, charge and stiffness of the materials to enhance tissue accumulation, adhesion, cellular uptake of nanoparticles and drugs are part of the strategy [23]. The results showed that the nanoparticles have a more rapid drug release rate in vitro than the micelles and they could easily penetrate into the cells due to higher specific surface area obtained by their mesoporous structure [25] which, not only serve as unique drug reservoirs but also have a part in multiphasic release systems. Some anticancer drugs like camptothecin and doxorubicin (DOX) are effective in chemotherapy but the applications in humans were limited due to the poor water solubility of the drug.…”
Section: Drug Targeting To Cancer Cells 21 Passive Targetingmentioning
confidence: 99%
“…The polyethyleneimine-polyethylene glycol (PEI-PEG) decoration on the surface of the nanoparticles was reported to decrease RES uptake and resulted in the retention of about 8% of the administered particle dose at tumor site [28]. The surface modifications of recent organic-inorganic silica hybrids with polymers are mostly based on PEG [27], PEI [28], PVP [29], chitosan [25] and poly-L-lactic acid (PLLA) [26] for drug targeting to cancer cell (Table 1). In one of the studies, PVP was used as a protecting polymer adsorbed on the surface of silica microspheres and NaOH was employed as an etching agent.…”
Section: Drug Targeting To Cancer Cells 21 Passive Targetingmentioning
confidence: 99%
See 1 more Smart Citation
“…Drugs such as bortezomib, the first clinically approved proteasome inhibitor, experienced limited efficacy due to its poor water-solubility and stability. Using and cytotoxicity of doxorubicin-loaded stearic acid-g-chitosan nanoparticles in A549 cells demonstrating faster cellular uptake with increased silica ratio [255]. Despite the advantages of ceramic nanoparticles in drug delivery and cancer therapy, questions have been raised about the potential toxic effects.…”
Section: Organic Nanoparticles For Lung Cancermentioning
confidence: 99%